Experimental Transplantation of Newborn Piglet Pancreatic Microfragments after Culturing or Hypothermal Storage in HTK Solution - Kopich, Yustiniya I.; Bozhok, Galina A.; Legach, Evgeniy I. (Problems of Cryobiology and Cryomedicine, 2015)
Subcutaneous transplantation of pancreas microfragments (PMFs) is regarded as an alternative approach for islets transplantation and applied in case of impossibility to derive ‘true’ islets from human fetal pancreas or tissue of neonatal animals (piglets, rabbits). The research involved the study of glucose level in rats with experimental I type Diabetes mellitus (DM) after trans-plantation of PMFs of neonatal piglets, as well as structural integrity of graft depending on its pre-treatment either by culturing or hypothermal storage (HS) in HTK solution (Custodiol®). After subcutaneous transplantation of PMFs of newborn piglets into rats with streptozotocin-induced DM the glucose level was normalized to the 45th day. After transplantation of PMFs being stored hypothermally in HTK solution a hyperglycemia weakening was observed similar to the one after the applying native PMFs. Using histological and morphometrical analysis a replacement of secretory tissue of pancreas to connective one was revealed in transplant to the 15th–22nd days, moreover the process was more intensive in cultured PMFs. Since glucose level in rats with DM was normalized without insulin-producing tissue of pancreas in transplant, the existence of specific factors resulting in stimulation of b-cell neogenesis in the recipient’s own gland was assumed. Probl Cryobiol Cryomed 2015; 25(1):45-56.